The ASAS-OMERACT core domain set for axial spondyloarthritis - Navarro-Compán, V.; Boel, A.; Boonen, A.; Mease, P.; Landewé, R.; Kiltz, U.; Dougados, M.; Baraliakos, X.; Bautista-Molano, W.; Carlier, H.; Chiowchanwisawakit, P.; Dagfinrud, H.; et al. (Seminars in arthritis and rheumatism, 2021)
The current core outcome set for ankylosing spondylitis (AS) has had only minor adaptations since its development 20 years ago. Considering the significant advances in this field during the preceding decades, an update of this core set is necessary. To update the ASAS-OMERACT core outcome set for AS into the ASAS-OMERACT core outcome set for axial spondyloarthritis (axSpA). Following OMERACT and COMET guidelines, an international working group representing key stakeholders (patients, rheumatologists, health professionals, pharmaceutical industry and drug regulatory agency representatives) defined the core domain set for axSpA. The development process consisted of: i) Identifying candidate domains using a systematic literature review and qualitative studies; ii) Selection of the most relevant domains for different stakeholders through a 3-round Delphi survey involving axSpA patients and axSpA experts; iii) Consensus and voting by ASAS; iv) Endorsement by OMERACT. Two scenarios are considered based on the type of therapy investigated in the trial: symptom modifying therapies and disease modifying therapies. The updated core outcome set for axSpA includes 7 mandatory domains for all trials (disease activity, pain, morning stiffness, fatigue, physical function, overall functioning and health, and adverse events including death). There are 3 additional domains (extra-musculoskeletal manifestations, peripheral manifestations and structural damage) that are mandatory for disease modifying therapies and important but optional for symptom modifying therapies. Finally, 3 other domains (spinal mobility, sleep, and work and employment) are defined as important but optional domains for all trials. The ASAS-OMERACT core domain set for AS has been updated into the ASAS-OMERACT core domain set for axSpA. The next step is the selection of instruments for each domain.